2017
DOI: 10.18632/oncotarget.14634
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of quiescent slow-cycling cells via reducing quiescence depth by natural compounds purified from Ganoderma lucidum

Abstract: The medical mushroom Ganoderma lucidum has long been used in traditional Chinese medicine and shown effective in the treatment of many diseases including cancer. Here we studied the cytotoxic effects of two natural compounds purified from Ganoderma lucidum, ergosterol peroxide and ganodermanondiol. We found that these two compounds exhibited cytotoxicity not only against fast proliferating cells, but on quiescent, slow-cycling cells. Using a fibroblast cell-quiescence model, we found that the cytotoxicity on q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 47 publications
(49 reference statements)
1
17
0
Order By: Relevance
“…For example, G. lucidum extractions were reported to have hepatoprotective effects and induce apoptosis of HepG2 cells 23. EP is a natural product present in G. lucidum , which has been shown to regulate various biological processes including oxidation,12 inflammation,24 and tumor cell growth 25…”
Section: Discussionmentioning
confidence: 99%
“…For example, G. lucidum extractions were reported to have hepatoprotective effects and induce apoptosis of HepG2 cells 23. EP is a natural product present in G. lucidum , which has been shown to regulate various biological processes including oxidation,12 inflammation,24 and tumor cell growth 25…”
Section: Discussionmentioning
confidence: 99%
“…Natural compounds purified from Ganoderma lucidum, ganodermanondiol, and ergosterol peroxide, play inhibitory roles via reducing the quiescence depth of cancer cells. Previous research has confirmed that these two compounds not only effectively inhibit rapidly proliferating cells but also activate the Rb-E2F bistable switch in quiescent slow-cycling cells, thereby reducing the quiescence depth of dormant cancer cells and enhancing their sensitivity to chemotherapeutic drugs [7]. Further studies on the effects of natural Ganoderma lucidum compounds on target quiescent cancer cells may present a new avenue for the development of novel chemotherapeutic agents.…”
Section: Reduction Of the Depth Of Cellular Quiescencementioning
confidence: 85%
“…Scientific literature to date supports the existence of quiescent cancer cells in many tumor types, including breast, liver and pancreatic cancer, acute myeloid leukaemia, melanoma, and glioblastoma [3,4]. In earlier studies, cells were induced to quiescence via serum starvation (whereby cells at low density were grown in serum-free medium) or contact inhibition (cells were grown in 10% serum until complete confluence) [5][6][7]. Quiescent cells were confirmed based on the lack of expression of Ki67 (a cell proliferation marker), negative EDU incorporation [7] or low rate of BrdU incorporation [3], and low Erk 1/2: p38 MAPK ratio [6][7][8].…”
Section: Quiescent Tumor Cells Represent a Clinical Problemmentioning
confidence: 99%
See 2 more Smart Citations